Kemampuan Mahasiswa PGSD dalam Merancang dan Melaksanakan Pembelajaran Berbasis High Order Of Thinking Skills - Kuntarto, Eko; Alirmansyah, Alirmansyah; Kurniawan, Agung Rimba (Jurnal Kiprah, 2019)
The results of a survey of the world body in the fields of writing, mathematics, and science as a measure of literacy progress, the results show the ability of high-level thinking or High Order of Thinking Skills (HOTS) students in Indonesia is low and is ranked 69 out of 76 countries. The results are a reflection of the renewal of the learning system in LPTK, including students in the Primary School Teacher Education (PGSD) study program. This research is a descriptive study because it describes the ability of PGSD students in planning and implementing HOTS-based learning in elementary schools. Respondents 154 people. The results showed the ability in basic knowledge of HOTS learning was still low, only 52.24% had passed. The remaining 47.76% did not meet the Minimum Mastery Criteria (KKM). The aspects of planning HOTS learning are still low, only 59.58% of students meet the KKM. Aspects of the ability to carry out HOTS-based learning, 49.03% of students do not meet the KKM. In the aspect of designing and implementing HOTS-based assessment, 51.30% did not reach the KKM. Conclusions of the study, the majority of students have not demonstrated good skills in planning and implementing HOTS learning in elementary schools.